Ideologies shaping university competition - Alajoutsijarvi, Kimmo; Kettunen, Kerttu; Pinheiro, Romulo (Taylor & Francis, 2025)
This conceptual study explores the dominant ideologies influencing the economic governance of higher education (HE) and shaping competition within the sector and among universities. It delineates and contrasts four key ideological positions - neoliberalism, managerialism, shareholderism, and stakeholderism - and outlines four corresponding types of university competition: signaling, intraorganizational, interorganizational, and priority competition. The paper contributes to the discourse on university competition as a macro trend in HE by examining its ideological underpinnings. Notably, it observes that real-life outcomes often diverge from the idealized visions these ideologies promote. The study concludes by illustrating how these four types of competition coexist in HE and discussing how shifts in coordination or decision-making mechanisms can influence which ideology gains prominence in shaping competition.